PRospective REgistry of PAtients in REfractory cardiogenic shock—The PREPARE CardShock registry. Issue 3 (13th July 2022) - von Lewinski, Dirk; Herold, Lukas; Stoffel, Christian; Pätzold, Sascha; Fruhwald, Friedrich; Altmanninger‐Sock, Siegfried; Kolesnik, Ewald; Wallner, Markus; Rainer, Peter; Bugger, Heiko; Verheyen, Nicolas; Rohrer, Ursula; et al.
Abstract: Aim: Cardiogenic shock (CS) is a hemodynamically complex multisystem syndrome associated with persistently high morbidity and mortality. As CS is characterized by progressive failure to provide adequate systemic perfusion, supporting end‐organ perfusion using mechanical circulatory support (MCS) seems intriguing. Since most patients with CS present in the catheterization laboratory, percutaneously implantable systems have the widest adoption in the field. We evaluated feasibility, outcomes, and complications after the introduction of a full‐percutaneous program for both the Impella CP device and venoarterial extracorporeal membrane oxygenator (VA‐ECMO). Methods: PREPARE CardShock (PRospective REgistry of PAtients in REfractory cardiogenic shock) is a prospective single‐center registry, including 248 consecutive patients between May 2019 and April 2021, who underwent cardiac catheterization and displayed advanced cardiogenic shock. The median age was 70 (58–77) years and 28% were female. Sixty‐five percent of the cases had cardiac arrest, of which 66% were out‐of‐hospital cardiac arrest. A local standard operating procedure (SOP) indicating indications as well as relative and absolute contraindications for different means of MCS (Impella CP or VA‐ECMO) was used to guide MCS use. The primary endpoint was in‐hospital death and secondary endpoints were spontaneous myocardial infarction and major bleedings during the hospital stay. Results: Overall mortality was 50.4% with a median survival of 2 (0–6) days. Significant independent predictors of mortality were cardiac arrest during the index event (odds ratio [OR] with 95% confidence interval [CI]: 2.53 [1.43–4.51]; p = 0.001), age > 65 years (OR: 2.05 [1.03–4.09]; p = 0.036]), pH < 7.30 (OR: 2.69 [1.56–4.66]; p < 0.001), and lactate levels > 2 mmol/L (OR: 4.51 [2.37–8.65]; p < 0.001). Conclusions: Conclusive SOPs assist target‐orientated MCS use in CS. This study provides guidance on the implementation, validation, and modification of newly established MCS programs to aid centers that are establishing such programs.